2013
DOI: 10.1063/1.4821429
|View full text |Cite
|
Sign up to set email alerts
|

Predicting a new photocatalyst and its electronic properties by density functional theory

Abstract: A new material CuBiW2O8 is reported here which is suitable for photocatalysts for solar-to-hydrogen generation by splitting water through photoelectrochemical approach. By density functional theory total energy calculations along with extensive mineral database search of relevant oxides, the crystal structures of CuBiW2O8 has been determined, which agrees well with the experimental result. We have analyzed the thermodynamical stability of this material. Its stability was found to be comparable to other well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…We chose this value of U eff to be consistent with the previous work of a Cu-Bi-O derived compuound. 55 A 9 x 9 x 13 Monkhorst-Pack 56 -point sampling was used for ion relaxation; however, density-of-states (DOS) and optical absorption calculations were done with higher 11 x 11 x 13 -point sampling. For the defect calculations, we constructed a supercell containing 112 atoms.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this value of U eff to be consistent with the previous work of a Cu-Bi-O derived compuound. 55 A 9 x 9 x 13 Monkhorst-Pack 56 -point sampling was used for ion relaxation; however, density-of-states (DOS) and optical absorption calculations were done with higher 11 x 11 x 13 -point sampling. For the defect calculations, we constructed a supercell containing 112 atoms.…”
Section: Discussionmentioning
confidence: 99%
“…Spin-polarized DFT calculations were performed with VASP. , Our calculations used the Heyd–Scuseria–Ernzerhof (HSE) hybrid functional to properly describe the Cu ions with oxidation state 2+ and open-shell 3d 9 orbitals in CuBi 2 O 4 . Previous first principles calculations for CuBi 2 O 4 , Cu–Bi–O-derived materials, and other p-type semiconductors with Cu 2+ ions such as CuO and CuAl 2 O 4 have used the generalized gradient approximation plus the Hubbard U (DFT + U ) approach with a large value of the Hubbard U parameter (∼7 eV) to correct the well-known DFT band gap underestimation. However, as shown below, we find that hybrid functionals are required to properly describe the electronic properties of CuBi 2 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the scientific studies on the electronic properties of pure and doped CuWO 4 have been mainly focused on the photocatalytic (PC) degradation of organic dyes (Rhodamine B, eosin yellow dye and methylene blue) under ultraviolet and visible light [53][54][55], magnetic [56][57][58][59], photoelectrochemical water splitting [60][61][62][63][64], visible and solar-assisted water splitting [65,66], photoanode for solar water oxidation [67,68], electrical transport [69], and photoluminescence (PL) [24,53,70]. An important point to be considered is that the theoretical studies [16,[71][72][73][74][75], performed by means of ab initio calculations based on the density-functional theory (DFT) for the electronic structure of CuWO 4 crystals, have shown that the conduction band (CB) of this oxide is composed of 3d orbitals (Cu atoms) and 5d orbitals (W atoms), while the valence band (VB) is formed of 2p orbitals (O atoms).…”
Section: Introductionmentioning
confidence: 99%